PRODUCTION OF DISHWASHING LIQUID FROM BANANA PEEL WASTE WITH THE ADDITION OF CALAMANSI ORANGE - Wica Elvina; Ulfah Anis (Fakultas Pertanian, 2025)
Banana peel is a by-product of banana fruit processing that has not been optimally utilized. This waste material tends to contribute to environmental pollution and can emit unpleasant odors. Despite being discarded, banana peel still contains active compounds such as pectin, lignin, cellulose, hemicellulose, tannins, flavonoids, saponin, and phenols. These compounds hold potential for use as raw materials in industrial products. Among them, saponins can serve as functional additives in the production of liquid soap. Saponins are chemical compounds known for their ability to produce foam when in contact with water, making them effective cleansing agents in soap formulations. The objective of this community service initiative is to provide knowledge and educational outreach to the residents of Banyumas Village, Kerkap Subdistrict, North Bengkulu Regency, regarding the utilization of banana peel waste as a primary ingredient in the production of dishwashing liquid. The methods employed in this program include coordination, public dissemination, lectures, and hands-on practical sessions. The activities involved the delivery of information on the potential uses of banana peel waste—which have yet to be widely explored by the local community—as well as instruction on the necessary tools and materials, and the step-by-step process for producing dishwashing liquid using banana peel and calamansi. Practical demonstrations were carried out by the implementing team. Participants were provided with detailed explanations regarding the functions of the tools and ingredients used, along with the procedural stages of soap-making. Informational handouts were also distributed to serve as references for independent practice. Additionally, time was allocated for open discussion, allowing participants to ask questions and offer feedback. The outcomes of this initiative indicated a high level of enthusiasm and engagement among participants, both during the instructional and practical components of the program.